1999
DOI: 10.1093/glycob/9.3.311
|View full text |Cite
|
Sign up to set email alerts
|

The sialylation of bronchial mucins secreted by patients suffering from cystic fibrosis or from chronic bronchitis is related to the severity of airway infection

Abstract: Bronchial mucins were purified from the sputum of 14 patients suffering from cystic fibrosis and 24 patients suffering from chronic bronchitis, using two CsBr density-gradient centrifugations. The presence of DNA in each secretion was used as an index to estimate the severity of infection and allowed to subdivide the mucins into four groups corresponding to infected or noninfected patients with cystic fibrosis, and to infected or noninfected patients with chronic bronchitis. All infected patients suffering fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
109
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 51 publications
15
109
0
1
Order By: Relevance
“…The present study measured total organic sulfate by hydrolysis and ion chromatography and confirmed the results by measuring bioavailable sulfur as growth yields relative to inorganic sulfate. The total organic sulfation levels in hydrolysed mucus glycoprotein fractions from CF patients, measured by Lo-Guidice et al (1994), ranged from 370 to 469 mmol g 21 , while Davril et al (1999) observed 3.1 % (w/ w) sulfate of purified bronchial mucin from CF patients, both of which are consistent with the values reported here.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study measured total organic sulfate by hydrolysis and ion chromatography and confirmed the results by measuring bioavailable sulfur as growth yields relative to inorganic sulfate. The total organic sulfation levels in hydrolysed mucus glycoprotein fractions from CF patients, measured by Lo-Guidice et al (1994), ranged from 370 to 469 mmol g 21 , while Davril et al (1999) observed 3.1 % (w/ w) sulfate of purified bronchial mucin from CF patients, both of which are consistent with the values reported here.…”
Section: Discussionsupporting
confidence: 91%
“…One notable change in lung secretions is the increased sulfation level that has been reported for mucins in the sputum of CF patients (Boat et al, 1976a;Chace et al, 1983;Davril et al, 1999;Xia et al, 2005). A positive correlation has been suggested between the level of sputum sulfation and the severity of disease in CF patients (Chace et al, 1983) and increased glycan sulfation has been proposed to occur as a response to bacterial infection, possibly to protect the underlying glycoprotein from enzymic degradation by bacteria (Corfield et al, 1993;Tsai et al, 1992Tsai et al, , 1995.…”
Section: Introductionmentioning
confidence: 94%
“…No characteristic changes in mucin composition have been found in CF that uniformly explain the basis of the aggregated luminal mucus in CF intestines, airways, exocrine glands, and reproductive organs. Certain changes in the carbohydrate side chains have been reported, such as alterations in fucosylation (1), sulfation (2,3), and sialylation (3), but these findings also occur in other chronic inflammatory states (3,4). Disulphide bonds, which are critical to the macromolecular structure of mucins, were not found to be significantly changed in CF mucus (5), nor is there evidence of increased synthesis of the major intestinal mucins Muc2 and Muc3 in CF mice compared with WT (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is now recognized that the CFTR channel is also required for bicarbonate (HCO 3 -) transport (14)(15)(16). Strikingly, the phenotype of the pancreas, perhaps the most acknowledged organ of HCO 3 -transport, segregates well with genotypes that severely disrupt CFTR-dependent HCO 3 transport in this organ and in the sweat duct (15,17). Likewise, HCO 3 -secretion is reduced in the CF intestine (16,18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation